Proposal for assignment of allele numbers for mobile colistin resistance (mcr) genes. (19th July 2018) - Partridge, Sally R; Di Pilato, Vincenzo; Doi, Yohei; Feldgarden, Michael; Haft, Daniel H; Klimke, William; Kumar-Singh, Samir; Liu, Jian-Hua; Malhotra-Kumar, Surbhi; Prasad, Arjun; Rossolini, Gian Maria; Schwarz, Stefan; et al.
Abstract: The initial report of the mcr-1 (m obile c olistin r esistance) gene has led to many reports of mcr-1 variants and other mcr genes from different bacterial species originating from human, animal and environmental samples in different geographical locations. Resistance gene nomenclature is complex and unfortunately problems such as different names being used for the same gene/protein or the same name being used for different genes/proteins are not uncommon. Registries exist for some families, such as bla (β-lactamase) genes, but there is as yet no agreed nomenclature scheme for mcr genes. The National Center for Biotechnology Information (NCBI) recently took over assigning bla allele numbers from the longstanding Lahey β-lactamase website and has agreed to do the same for mcr genes. Here, we propose a nomenclature scheme that we hope will be acceptable to researchers in this area and that will reduce future confusion.